Handbook of isoelectric focusing and proteomics (Elsevier Academic Press, 2005)
This highly practical book also contains chapters on alternative methods that may pave the way in the search for efficient techniques for fractionating and purifying proteins. Complete with the history of IEF focusing to authors' insights and practical tips, this book is a must for anyone working in proteomics. It is the only current book available on the subject. It includes author insights and practical tips. It is an ideal single source for students and researchers working in proteomics.